Manipulation of intertrochanteric fractures in patients with below- or above-knee amputation using a fracture table: Two case reports. Issue 2 (15th January 2021) - Lee, Sang-Min; Suh, Kuen Tak; Oh, Young Kwang; Shin, Won Chul
Abstract: Rationale: In general, in the case of an intertrochanteric hip fracture, surgery is performed using a fracture table and by fixing the patient's foot to the boot piece. In patients with amputation of the affected lower limb, it is impossible to fix the foot to the boot piece; therefore, the traction and rotation of the fracture site cannot be maintained, leading to improper patient positioning. In such cases, a fracture table cannot be used intraoperatively to stabilize the fracture site. We report 2 cases of successful intertrochanteric fracture reduction using a fracture table for patients with below- or above-knee amputation. Patient's concerns: Both patients presented with left hip pain resulting from a fall. Diagnosis: Two elderly male patients with prior limb amputations below or above the knee presented with intertrochanteric hip fractures. Previous amputation of the lower limb on the same side of the fracture made it difficult to use a fracture table intraoperatively to stabilize the fracture site. Intervention: We performed fracture reduction using a modified fracture table for each patient. By altering the rotation of the boot piece and using additional skin traction bands, we could maintain proper patient positioning and rotation direction and obtain sufficient traction force. Outcomes: The chosen outcomes were fracture alignment and union at the end of follow-up and the ability to walk and perform activities of daily living. Reduction and intramedullary nail fixation using the fracture table were successful in both cases. Appropriate fracture union was achieved within 6 months, and the preoperative walking ability and activities of daily living were recovered in both patients, who were followed-up for 28 and 24 months. Lessons: Modification of the usual fracture table to suit patients with lower limb amputation helped us successfully perform intertrochanteric hip fracture surgery with the usual levels of traction and rotation required of the fracture site.